Sexual segregation in Indo-Pacific bottlenose dolphins is driven by female avoidance of males. (23rd December 2017) - Galezo, Allison A; Krzyszczyk, Ewa; Mann, Janet
Abstract : In many species, males and females segregate from each other because they allocate time differently, forage on different foods, or tolerate predators differently. In Indo-Pacific bottlenose dolphins, male aggression can deter mixed-sex groups. When males and females encounter each other, males often join females while females often leave males. Females likely evade males to avoid aggression. Abstract: Sexual segregation is widespread in mammals, although the proximate causes are poorly understood in monomorphic species. Indo-Pacific bottlenose dolphins ( Tursiops aduncus ), which exhibit a high degree of fission–fusion dynamics, offer a useful lens to examine the ecological and social drivers of sexual segregation. While ecological hypotheses suggest that sexual segregation is a by-product of sex-specific ecological preferences (e.g., related to habitat, foraging, or predator avoidance), the social hypothesis proffers that segregation results from same-sex preferences (e.g., due to cooperative benefits) and/or opposite-sex avoidance (e.g., due to competitive or exploitative interactions). Indo-Pacific bottlenose dolphin females range from nearly solitary to highly sociable. Males associate in alliances that cooperate to sequester individual females and exclude competing males. Given evidence for allied sexual coercion, our primary hypothesis was that sexual segregation is driven by female avoidance of aggressive males. However, given robust evidence for sex-biased foraging tactics, ecological factors likely also contribute. Using the Sexual Segregation and Aggregation Statistic with 17, 468 sighting records spanning 31 years, we found strong sexual segregation. Unique to our work, we analyzed the direction of joins and leaves between males and females from focal observations ( N = 10, 715 fission–fusion events, 87 females, 111 males) to determine which sex drives sexual segregation. Females drove segregation by rarely joining and often leaving males. Although ecological factors likely reinforce sexual segregation, social factors predominate. This study demonstrates a sex-bias in fission–fusion dynamics in a socially complex wild mammal population and offers strong empirical support to the social hypothesis of sexual segregation.